Faktor-faktor Yang Mempengaruhi Kinerja Manajerial (Studi Kasus Pada PT. Radar Lampung Group) - Luthfi, Muhammad; Sariningsih, Eka; Arafat, Yaseer (Universitas Malahayati, 2020)
This study aims to analyze the factors that influence managerial performance. These factors includethe budget planning system, budgeting participation, budgeting schedule, clarity of budget targets,internal control and compensation at PT. Radar Lampung Group.Data was collected by Purposive Sampling, with a sample of 42 respondents involved in budgetingand procurement of goods. The results of data analysis were tested using SmartPLS 3.0 Partial LeastSquare (PLS).The test results show the system of budget planning, budgeting schedule, clarity ofbudget targets, internal control has an influence on managerial performance. While budgetaryparticipation and compensation do not affect managerial performance. The results of the testcoefficient of determination (R2) are around 0.542.Keywords: Budget planning system, budgeting participation, budgeting schedule, clarity of budgetgoals, internal control, compensation and managerial performance.